Effect of phototherapy on event-related potentials in patients with post-stroke depression through serum tetrahydrobiopterin level intervention: a clinical study - Bingchuan Xie; Zhenguo Wu; Zixuan Zhou; Wenting Lu; Lin Liu; Lizhuang Zhang (BMC Psychiatry)
Abstract Background This study investigated the effects of phototherapy on serum BH4 levels, evoked potentials, and cognitive impairment in post-stroke depression patients. Methods We conducted a prospective study with 160 post-stroke depression patients, randomly assigned to an experimental group receiving daily 40 min of phototherapy alongside routine treatment, and a control group receiving only routine treatment. Serum tetrahydrobiopterin (BH4) levels were measured via ELISA. Evoked potentials were assessed using an ERP recorder, depressive symptoms were evaluated with the Hamilton Depression Scale (HAM-D), and cognitive function was analyzed using the Montreal Cognitive Assessment (MoCA). Inflammatory factor expression was detected via RT-PCR. Results Both groups exhibited increased BH4 levels, but the phototherapy group had significantly higher levels (P < 0.05). The phototherapy group also demonstrated improved ERP parameters, with higher MMN latency, P300 latency, and amplitudes compared to controls (P < 0.05). HAM-D scores decreased more in the phototherapy group (P < 0.05), while MoCA scores increased significantly (P < 0.05). Additionally, inflammatory markers IL-6, TNF-α, and IL-1β were lower in the phototherapy group (P < 0.05). Conclusions Phototherapy positively influenced BH4 levels, improved evoked potentials, alleviated depressive symptoms, enhanced cognitive function, and reduced inflammation in post-stroke depression patients.